2018
DOI: 10.1007/s11934-018-0771-6
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Management of Urethral Stricture: Review and Practice Algorithm for Management of Male Urethral Stricture Disease

Abstract: Older studies quoted high rates of success with endoscopic management of urethral stricture, including repeated DVIU. There is now evidence to support a limited role of endoscopic intervention in the management of urethral stricture, and especially strong evidence that repeated endoscopic procedures are not effective. There is poor evidence to support the long-term efficacy of endoscopic urethral stricture management. Furthermore, novel advances in adjunctive therapies have not yet demonstrated durable patency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…The 95% CI did not exceed the reference 65% success rate for men with 0-1 prior dilations in the Steenkamp and Heyns study, but did exceed the reference 10% rate for men with 2 prior dilations. 3 Secondary outcome measures demonstrated an improvement in urinary symptoms, urinary quality of life, pain scores, and uroflowmetry-specifically Qmax, and PVR. Sexual function was not significantly affected by DCB.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The 95% CI did not exceed the reference 65% success rate for men with 0-1 prior dilations in the Steenkamp and Heyns study, but did exceed the reference 10% rate for men with 2 prior dilations. 3 Secondary outcome measures demonstrated an improvement in urinary symptoms, urinary quality of life, pain scores, and uroflowmetry-specifically Qmax, and PVR. Sexual function was not significantly affected by DCB.…”
Section: Discussionmentioning
confidence: 97%
“…2 A recent review demonstrated a 90% lifetime recurrence rate, even for first time dilations, and near 100% for repeat dilations. 3 Dilation and DVIU have similar outcomes, whereas urethroplasty has the highest rate of success. 4,5,6,7 Steroid or mitomycin C (MMC) injection have been used as an adjuvant to endoscopic treatment, but results have been mixed.…”
Section: Introductionmentioning
confidence: 98%
“…5 Injury of the corpus spongiosum during DVIU can also result in the development of perineal hematoma and urethral hemorrhage. 44 Peri-operative infection has been reported to significantly increase stricture recurrence. 25 Thus, DVIU should be covered by prophylactic antibiotics.…”
Section: Complications Of Dviumentioning
confidence: 99%
“…3,[9][10][11] However, for many patients USD recurrence is a likely outcome of the initial procedure, particularly with endoscopic management options. Recurrence rates following endoscopic treatments range between 23 and 92%, 5,12 and are even higher with multiple endoscopic procedures, eventually approaching 100%. 6,13,14 Across all studies, risk factors for USD recurrence include stricture length, smoking, obesity, diabetes mellitus, congenital malformation such as hypospadias, presence of chronic inflammatory conditions such as lichen sclerosus (LS), and previous attempts at management, particularly with augmentation or substitution urethroplasty.…”
Section: Introductionmentioning
confidence: 99%